2019
DOI: 10.4103/ajns.ajns_165_19
|View full text |Cite
|
Sign up to set email alerts
|

One-stage operation with ipsilateral two-piece craniotomies for a case of subarachnoid hemorrhage with multiple intracranial aneurysms

Abstract: Subarachnoid hemorrhage (SAH) with multiple intracranial aneurysms is common, but the difficulties often arise in determining treatment strategy in the acute phase. We experienced a case of SAH with distal anterior cerebral artery aneurysm coexisting with middle cerebral artery and anterior communicating artery aneurysms, in which it was difficult to identify the precise rupture site preoperatively, and both pterional approach and interhemispheric approach were required in the acute phase of SAH. However, we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…This study only targeted mUIAs; therefore, caution should be exercised when OSMC are applied to aneurysmal subarachnoid hemorrhage (aSAH) patients with MIAs. Although some studies have reported OSMC in patients with multiple aneurysms and aSAH who underwent emergency surgery [20,28,31], we propose that the use of OSMC should be considered carefully because brain relaxation is di cult. This study is the result of an analysis of the surgeries performed in a single, large-scale, neurovascular center in Korea.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This study only targeted mUIAs; therefore, caution should be exercised when OSMC are applied to aneurysmal subarachnoid hemorrhage (aSAH) patients with MIAs. Although some studies have reported OSMC in patients with multiple aneurysms and aSAH who underwent emergency surgery [20,28,31], we propose that the use of OSMC should be considered carefully because brain relaxation is di cult. This study is the result of an analysis of the surgeries performed in a single, large-scale, neurovascular center in Korea.…”
Section: Discussionmentioning
confidence: 93%
“…Multiple intracranial aneurysms (MIAs) account for 7-35% of diagnosed intracranial aneurysms [15,23,26], and have a higher risk of rupture than single intracranial aneurysms [13,31]. Therefore, multiple unruptured intracranial aneurysms (mUIAs) require active treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple intracranial aneurysms (MIAs) account for 7-35% of diagnosed intracranial aneurysms [15,23,26], and have a higher risk of rupture than single intracranial aneurysms [13,31]. Therefore, multiple unruptured intracranial aneurysms (mUIAs) require active treatment.…”
Section: Introductionmentioning
confidence: 99%
“…If all of the mUIAs cannot be treated with one approach, staged operations should be considered [30,34]. Although it is uncommon, there have been cases in which two or more craniotomy procedures were performed using one incision [5,11,31]. There few studies on bilateral craniotomy, most of which are case reports [6,7,12,20,28].…”
Section: Introductionmentioning
confidence: 99%